Evolution of particle number size distribution in an urban atmosphere during episodes of heavy pollution and new particle formation - ZJ Wu; Hu, M.; Yue, D. L.; Wehner, B.; Wiedensohler, A. (Science China-Earth Sciences, 2011)
This study discusses the evolution of particle number size distribution during episodes of heavy pollution and new particle formation in the urban atmosphere of Beijing to quantify the effects of dynamic processes (coagulation and condensation) on the particle number size distribution. During a heavy-pollution event, an extremely low number concentration of 3-10 nm particles (on average 46 cm(-3)) was observed. This is because nucleation-mode particles were easily removed by strong coagulational scavenging of larger particles under this condition. In addition, a large condensation sink (on average 0.13 s(-1)) restrained nucleation, which is one of the major sources of nucleation-mode particles. Conversely, during a new-particle formation event, the small condensation sink (0.01 s(-1)) of precursor facilitated nucleation. At the same time, preexisting particles had little ability to scavenge newly formed particles (around 1 nm) and allowed them to grow to a detectable size (larger than 3 nm currently). We suggest that the effects of dynamic processes (coagulation and condensation) on particle size distribution should be stressed under some extreme conditions of the relatively polluted urban atmosphere in addition to traffic and meteorological factors.
Keywords: aerosol; and condensation sinks; coagulation; Geology; growth; mode particles; new particle formation; nucleation; Particle number size distribution; particulate air-pollution; rates